Gelombang Otak dalam Pembelajaran Kontemporer Pendidikan Agama Islam - Idawati, Khoirotul; Hanifudin (Program Studi Magister Pendidikan Agama Islam Universitas Hasyim Asy’ari Tebuireng Jombang m Asy'ari, 2026)
Islamic Religious Education (IRE) is not only oriented toward the transmission of religious knowledge but also toward the development of students’ character, religious awareness, and spiritual experience. However, IRE practices are still predominantly characterized by cognitive and memorization-based approaches, with limited attention to learners’ neurobiological readiness and psychological conditions. This study aims to analyze the role of brainwave patterns in contemporary Islamic Religious Education and to formulate a conceptual framework for integrating neuroscience into Islamic education. The study employed a qualitative approach using a library research method through the analysis and synthesis of literature on neuroscience, neurospirituality, the epistemology of Islamic education, and the pedagogical interpretation of Qur'an Surah An-Nahl verse 125. The findings indicate that Delta, Theta, Alpha, Beta, and Gamma brainwaves each make distinct pedagogical contributions, ranging from biological restoration, reflective and contemplative activities, the creation of a comfortable and focused learning environment, the development of analytical thinking, to the integration of complex information and higher-order thinking skills. Furthermore, the principles of bil hikmah (wisdom), mau'izhah hasanah (good instruction), and mujādalah billatī hiya ahsan (the best manner of dialogue) are aligned with learning approaches that emphasize neurobiological readiness, affective engagement, and meaningful educational dialogue. This study proposes a brainwave-based conceptual framework for Islamic Religious Education that integrates neurobiological readiness, religious consciousness, and the educational orientations of ta'lim, tarbiyah, ta'dib, and tazkiyah.